Concentration of thyroxine-binding globulin: value of direct assay. Issue 6059 (19th February 1977) - Burr, W A; Ramsden, D B; Evans, S E; Hogan, T; Hoffenberg, R
Abstract : The concentration of thyroxine-binding globulin (TBG) in the serum can now be measured by direct assays that are simple and inexpensive. Comparison of a direct measurement of TBG concentration with a widely used indirect method (Thyopac-3) showed that the indirect method was inaccurate when TBG concentrations were high. This will result in an increase in the derived free thyroxine index (FTI), so that euthyroid patients with a raised TBG concentration may be at risk of being labelled thyrotoxic. Correction of serum total thyroxine (T4) concentration according to the actual TBG concentration (T4:TBG ratio) provided a better correlation with thyroid state than FTI.